Relación del liderazgo de la directora y el desempeño laboral de las docentes de la I.E.I. N° 87 Callao 2009 - Castillo Vásquez, Verónica Dalila (2010)
This research presents a descriptive correlational study to determine the relationship between the leadership style of the director and job performance of teachers in the Educational Institution Home Santa Rosa No. 87. The sample included a total of 110 parents randomly chosen from the classrooms of children ages 3, 4 and 5 years of age and 11 teachers who work in the institution. A first survey was administered to parents to know their perception about the leadership style of the director and the job performance of teachers. After a second survey was applied to the teachers to know the style of lesdership they perceived of the director. Finally third self-assessment survey their performance. The results revealed that there is not relationship between the leadership style of the director and job performance of teachers. These results are discussed in the context of the investigation.